2005
DOI: 10.1017/s1472928807000258
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between neocortical and hippocampal networks via slow oscillations

Abstract: Both the thalamocortical and limbic systems generate a variety of brain state-dependent rhythms but the relationship between the oscillatory families is not well understood. Transfer of information across structures can be controlled by the offset oscillations. We suggest that slow oscillation of the neocortex, which was discovered by Mircea Steriade, temporally coordinates the self-organized oscillations in the neocortex, entorhinal cortex, subiculum and hippocampus. Transient coupling between rhythms can gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
219
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(237 citation statements)
references
References 196 publications
(276 reference statements)
11
219
2
Order By: Relevance
“…1), if infraslow signals are taken to represent the lowfrequency component of the model and δ-band activity is viewed as the higher frequency component. These results represent a departure from rodent hippocampus studies, which associate δ/θ activity with low-frequency signaling, and γ/sharp-wave activity with higher frequency signals (26)(27)(28)(29). We speculate that the differences may be attributable to cross-species effects (16) as well as different signaling processes captured by macro-as opposed to microelectrode recordings (30) (discussed further in Hippocampal Delta, below).…”
Section: Discussionmentioning
confidence: 78%
“…1), if infraslow signals are taken to represent the lowfrequency component of the model and δ-band activity is viewed as the higher frequency component. These results represent a departure from rodent hippocampus studies, which associate δ/θ activity with low-frequency signaling, and γ/sharp-wave activity with higher frequency signals (26)(27)(28)(29). We speculate that the differences may be attributable to cross-species effects (16) as well as different signaling processes captured by macro-as opposed to microelectrode recordings (30) (discussed further in Hippocampal Delta, below).…”
Section: Discussionmentioning
confidence: 78%
“…Buzsaki et al (1988), for example, showed that unilateral lesion of the thalamus did not change power spectrum in the 1-4 Hz band of EEG activity. Nonetheless, a clear mechanistic account from this approach is unlikely because these oscillations reflect a complex system in which cortical and subcortical areas are likely cooperatively involved through reciprocal connections (Steriade and Timofeev, 2003;Sirota and Buzsáki, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, slow waves may represent global or traveling wave-mediated changes in activity that entrain much of the cortex (Massimini et al, 2004). Multichannel EEG recordings have proven useful in addressing these hypotheses and have shown both local patterns of cortical up/down state (Sirota and Buzsáki, 2005) and widespread synchrony (Buzsaki et al, 1988) of cortical slow-wave activity. However, these approaches have been unable to resolve the regional structure and dynamics of these waves because of relatively sparse sampling.…”
Section: Introductionmentioning
confidence: 99%
“…The conflict arises because A and B are known to belong together as a pair, but now B is also being paired with C. Introduction of this conflicting information is thought to reactivate the previously learned pair (A-B) as well. Resolution of this conflict has been shown to involve an increase in connectivity between the hippocampus and the vmPFC (van Kesteren, Fernández, Norris, & Hermans, 2010;Zeithamova, Dominick, & Preston, 2012), with activity in the vmPFC phase locked to hippocampal theta oscillations that are prominent both in waking activity and during rapid eye movement (REM) sleep (Sirota & Buzsáki, 2005). Furthermore, the degree of activation of the vmPFC and hippocampus during this conflict predicts the successful formation of indirect, relational associations (A-C), which resolves the conflict by incorporating how B is related to A and C and defining the relationship between all three components (van Kesteren et al, 2010;Zeithamova et al, 2012).…”
Section: Direct Associative Memories and Relational Memory Formationmentioning
confidence: 99%